Does Radiographic Coxa Profunda Indicate Increased Acetabular Coverage or Depth in Hip Dysplasia?. Issue 6 (June 2015) - Fujii, Masanori; Nakamura, Tetsuro; Hara, Toshihiko; Nakashima, Yasuharu; Iwamoto, Yukihide
Abstract: Background: Although radiographic coxa profunda has been considered an indicator of acetabular overcoverage, recent studies suggest that radiographic coxa profunda is a nonspecific finding seen even in hip dysplasia. The morphologic features of coxa profunda in hip dysplasia and the frequency with which the two overlap are not well defined. Questions/purposes: We determined (1) the prevalence of radiographic coxa profunda in patients with hip dysplasia; (2) the morphologic differences of the acetabulum and pelvis between patients with hip dysplasia and control subjects; and (3) the morphologic differences between hip dysplasia with and without coxa profunda. Methods: We retrospectively reviewed the pelvic radiographs and CT scans of 70 patients (70 hips) with hip dysplasia. Forty normal hips were used as controls. Normal hips were defined as those with a lateral center‐edge angle between 25° and 40°. Coxa profunda was defined as present when the acetabular fossa was observed to touch or was medial to the ilioischial line on an AP pelvic radiograph. CT measurements included acetabular version, acetabular coverage, acetabular depth, and rotational alignment of the innominate bone. Results: The prevalence of coxa profunda was 44% (31 of 70 hips) in dysplastic hips and 73% (29 of 40 hips) in the control hips (odds ratio, 3.32; 95% CI, 1.43‐7.68). Dysplastic hips had a more anteverted and globally shallow acetabulum with inwardly rotated innominate bone compared with the control hips (p < 0.001). Dysplastic hips with coxa profunda had a more anteverted acetabulum (p < 0.001) and inwardly rotated innominate bone (p < 0.002) compared with those without coxa profunda, whereas the acetabular coverage and depth did not differ between the two groups, with the numbers available. Conclusions: Radiographic coxa profunda was not a sign of increased acetabular coverage and depth in patients with hip dysplasia, but rather indicates classic acetabular dysplasia, defined by an anteverted acetabulum with anterolateral acetabular deficiency and an inwardly rotated pelvis. Thus, the presence of coxa profunda does not indicate a disease in addition to hip dysplasia, and the conventional maneuvers during periacetabular osteotomy are adequate for these patients. Level of Evidence: Level IV, diagnostic study.